Competing constructions of British national identity: British newspaper comment on the 2012 Olympics opening ceremony. (April 2015) - Thomas, Ryan J; Antony, Mary Grace
This study used newspaper comment on the opening ceremony of the 2012 Olympic Games in London as an avenue to discuss and contemplate British national identity. Through analysis of 91 editorials and opinion columns in the British national press, we uncovered three prominent themes in newspaper discourse: the 'greatness' of Great Britain, the ceremony as a symbol of contemporary political contestation, and the difficulties of defining and articulating a coherent, 'catch-all' definition of British identity. These results are demonstrative of the inherent challenge to connect multiple and contradictory conceptualizations of national identity into a coherent whole.